The Asset Allocation of Santisuk 9D Village in Buddhism - Saiuneam, Karisa; Thangthongmadan, Sathien; Pimprasan, Supot; Cittatanto, Phrapalat Chakkris (Academic MCU Buriram Journal, 2023)
The academic articles on Asset Allocation of Santisuk (Peace) 9D Village in Buddhism had two objectives: 1) to study the background of the establishment of the self-reliant fund in Santisuk 9D Village; 2) found The Self-Sufficient Village Fund was established from the idea of raising funds to solve local community problems. Its purpose is to create a virtuous society where everyone can live happily together and create guidelines for solving social problems at the village level to achieve the common objectives of the people in the village asset allocation of Santisuk village 9D in the part of the Buddhist Village fund on the principle of Phokatiya (Utilizing wealth) is the principle of expenditure for the maximum benefit of the fund’s property services, namely: (1) raise oneself to be happy; using village funds for village development (2) raising friends to be happy; allocating assets for use in the committee’s activities to create a harmonious community generosity (3) Prevention of danger and keep it for use when sick; the village fund has allocated a portion of its assets to help the victims, underprivileged and other welfare in the community (4) to make the fivefold offering; part of the village fund will be allocated for public charity (5) to uphold Buddhism. The Body of knowledge gained is to raise oneself to be happy for the development of the village, generate income for the community, raise friends to create a supportive community, increase kindness, and create a Thai way of unity, to prevent danger to help the victims, make the fivefold offering sacrifice for public charity, uphold Buddhism for the happiness and peace of the community.